Freirean hope as educational construct for teacher education in South Africa - Beryl Verna Botman (UFMG, 2021)
This article argues that South African teacher education and development policy lack an explicit philosophy of education and corresponding pedagogy that promote transformation and equality. After an analysis of some works by Paulo Freire, it is argued that it is in a Freirean philosophy of education and in a pedagogy of hope that the praxis of teacher education establishes the notion of teachers as unfinished beings and agents of hope. This article offers an opportunity to imagine what Freire's Pedagogy of hope (FREIRE, 1994) could contribute to the dialogue regarding the policy, gazetted in 2011 and revised in 2015, on the minimum requirements for teacher education qualifications in South Africa. The fundamental role that teacher education institutions can play in contributing to the transformation of education is defended, particularly if the philosophy of Freirean education and a pedagogy of hope are compromised. The article concludes with an attempt at re-orientation of teacher education policy.